Factors Associated with Stress Levels among Professional Nursing Students at the Institute of Health Sciences Pelamonia Makassar - Zakariah Pratama; Nasrullah Nasrullah; Hasbullah Habullah; Nurun Salaman Alhidayat (Ammar Dharma Foundation, 2026)
Background: Professional nursing students are exposed to demanding academic and clinical responsibilities that may increase stress levels and negatively impact mental health, academic achievement, and clinical performance. Identifying stress-related factors is crucial to support students throughout their professional education.Objective: This study aimed to analyze the factors associated with stress levels among professional nursing students at the Institute of Health Sciences Pelamonia Makassar.Methods: This study employed a quantitative analytical approach with a cross-sectional design conducted from August to September 2025. The study population included 112 professional nursing students selected using a total sampling technique. Data were collected through a structured questionnaire measuring stress associated with patient care, clinical instructors and nursing staff, academic tasks and workload, peers and daily life, lack of knowledge and skills, and the clinical practice environment. Stress levels were classified as mild, moderate, and severe. The Chi-square test was used for data analysis.Results: The results demonstrated that stress related to clinical instructors and nursing staff, academic tasks and workload, peers and daily life, lack of knowledge and skills, and the clinical practice environment were significantly associated with students’ stress levels (p < 0.05). However, stress related to patient care showed no significant association with stress levels (p > 0.05).Conclusion: Academic, social, and environmental factors predominantly influence stress levels among professional nursing students. Therefore, strengthening academic support, improving clinical supervision, and fostering a supportive clinical learning environment are recommended to help reduce student stress.